2008
DOI: 10.1002/adsc.200800364
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Synthesis of 1,2‐Disubstituted Cyclopentanes from 1,6‐Dienes by Ring‐Closing Kharasch Addition of Carbon Tetrachloride

Abstract: The reaction of carbon tetrachloride (CCl 4 ) with various 1,6-heptadienes catalyzed by copper homoscorpionate complexes affords cyclization products in moderate to high yields. The process involves the addition of the trichloromethyl radical to the diene followed by a 5-exo-trig cyclization reaction, resulting in the formation of the cis-3-chloromethyl-4-(2,2,2-trichloroethyl)cyclopentane isomers in a highly regiospecific and stereospecific manner.We have studied the use of magnesium (Mg) as reducing agent fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 70 publications
0
31
0
1
Order By: Relevance
“…16 Additionally, they found that when Mg was added as a reducing agent, they observed improved yields. This radical/radical process is initiated by abstraction of a chlorine atom from CCl 4 .…”
Section: Transition Metal-mediated Domino Reactionsmentioning
confidence: 99%
“…16 Additionally, they found that when Mg was added as a reducing agent, they observed improved yields. This radical/radical process is initiated by abstraction of a chlorine atom from CCl 4 .…”
Section: Transition Metal-mediated Domino Reactionsmentioning
confidence: 99%
“…Both processes originated from well-known Kharasch addition in which polyhalogenated compounds were added to alkenes via free-radical means (13,39,40). Recent studies have also indicated that TPMA is a superior complexing ligand in ATRA (13,33,40,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54) and ATRP (49,(55)(56)(57)(58) that utilize reducing agents. The role of a reducing agent in both systems is to continuously regenerate the activator species (copper(I) complex) from the corresponding deactivator (copper(II) complex).…”
Section: Catalysis With Transition Metal Complexes Containing Tpma LImentioning
confidence: 97%
“…Over the past five years, catalyst regeneration in ATRA has attracted considerable academic interest (Blackman, 2008;Díaz-Álvarez et al, 2008;Eckenhoff & Pintauer, 2010a;Iizuka et al, 2007;Lundgren et al, 2008;Maiti et al, 2008;Oe & Uozumi, 2008;Pintauer, 2010;Thommes et al, 2007;Wallentin et al, 2012;Wolf et al, 2008) and was successfully applied to intramolecular ATRA or atom transfer radical cyclization (ATRC) and sequential ATRA followed by [3+2] azide-alkyne cycloaddition reactions (Clark & Wilson, 2008;Muñoz-Molina et al, 2008;Nguyen et al, 2011;Sebren et al, 2014;Thommes et al, 2007;Wolf et al, 2008).…”
Section: Towards Diminishing Concentrations Of Copper Catalysts In Atmentioning
confidence: 99%
“…For a given transition metal, this is typically achieved using a complexing ligand. In case of copper, neutral nitrogen based ligands are typically used, ranging from bidentate (2,2 -bipyridine (bpy) (Pirrung et al, 1993(Pirrung et al, , 1994(Pirrung et al, , 1995 and N-alkyl-2-pyridylmethanimine (NAlkPMI) (Clark, 2002;Clark et al, 2000Clark et al, , 2001aClark et al, , 2001bHaddleton et al, 1997aHaddleton et al, , 1997bHaddleton et al, , 1998Lad et al, 2003), tridentate (N,N,N ,N ,N -pentamethyldiethyelenetriamine (PMDETA) (Benedetti et al, 1997;Ghelfi et al, 1999;Ghelfi & Parsons, 2000) and trispyrazolyl borate (Tp x ) (Muñoz- Molina et al, 2007Molina et al, , 2008, tetradentate (1,1,4,7,10,10-hexamethyltriethylenetetramine (HMTETA) , tris[2-(dimethylaminoethyl]amine (Me 6 TREN) (Clark et al, 1999(Clark et al, , 2000(Clark et al, , 2001bEckenhoff & Pintauer, 2011) and TPMA (De Campo et al, 1999, 2000Eckenhoff et al, 2012;Eckenhoff & Pintauer, 2007, 2010a, 2010b to multidentate (N,N,N ,N -tetrakis(pyridin-2-ylmethyl)ethylenediamine (TPEDA) (De Campo et al, 1999, 2000Kaur et al, 2015a). Representative examples of molecular structures of copper(I) (activators) and copper(II) (deactivators) complexes commonly used in ATRA and ATRP are shown in Fig.…”
Section: Basic Components Of Transition Metal Catalyzed Atom Transfermentioning
confidence: 99%